Estudio bibliográfico de tres tipos de desamargado (tradicional, fermentaciòn y germinaciòn) en diferentes índices de madurez de Chocho (lupinus mutabilis sweet) en dos variedades (andino iniap 450 y guaranguito iniap 451) para determinar su eficacia. - Quitio Amangandi, Edgar David (2020)
This research project contains a bibliographic compilation of high impact sources of the food industry and research previously conceived by the Training Project for Harvest and Post- Harvest Management (Andean Grains) by the Technical University of Cotopaxi of the Faculty of (CAREN). In which three different methodologies for reducing the alkaloid content of lupine are presented in two varieties (Andino INIAP 450 and Guaranguito INIAP 451) in different maturity index: tender and dry, with the objective of determining which of the three debittering methods It is the most effective when it comes to reducing the content of alkaloids present in lupine, since these substances are toxic for those who consume it, for this the Ecuadorian regulations are taken into account as a basis (NTE INEN 2390: LEGUMES. GRAIN DEBITTERING OF LUPINE. REQUIREMENTS, 2004, p. 2), where it must comply with the physical-chemical analysis such as the determination of (percentage of alkaloids, pH, moisture and protein) and microbiological such as (total coliforms, fungi and yeasts, and Escherichia coli), to be considered an effective debittering method it must be within the ranges required by the regulations, after the bibliographic compilation, the best extraction methods were analyzed d and alkaloids, according to the effectiveness of each one and an effective debittering method is determined. In addition, a table of costs of the best treatment was prepared with the two varieties, with the two maturity indices taking into consideration the materials, equipment and supplies that intervene in the most effective debittering method. Then the methods of the 4 agri- food proposals were founded, such as: fritters, fermented drink, empanadas and tempeh using the two varieties of lupine in a tender and dry state where they were outlined in flow diagrams. Keywords: lupine, debittering, effective, varieties, maturity, alkaloids